2004
DOI: 10.1210/er.2002-0032
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor in Prostate Cancer

Abstract: The normal development and maintenance of the prostate is dependent on androgen acting through the androgen receptor (AR). AR remains important in the development and progression of prostate cancer. AR expression is maintained throughout prostate cancer progression, and the majority of androgen-independent or hormone refractory prostate cancers express AR. Mutation of AR, especially mutations that result in a relaxation of AR ligand specificity, may contribute to the progression of prostate cancer and the fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
1,402
2
21

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,511 publications
(1,448 citation statements)
references
References 351 publications
(282 reference statements)
23
1,402
2
21
Order By: Relevance
“…That may mean that distant metastasis was actually the cause of death. AR plays an important role in the development of prostate cancer and can be observed in primary prostate cancer and detected throughout the progression of both hormone-sensitive and hormone-refractory cancers [20,21]. In this study, AR expression was reduced in epithelial and stromal cells 1-week postcastration, which was the normal short-term response to castration in TRAMP mice.…”
Section: Discussionsupporting
confidence: 46%
“…That may mean that distant metastasis was actually the cause of death. AR plays an important role in the development of prostate cancer and can be observed in primary prostate cancer and detected throughout the progression of both hormone-sensitive and hormone-refractory cancers [20,21]. In this study, AR expression was reduced in epithelial and stromal cells 1-week postcastration, which was the normal short-term response to castration in TRAMP mice.…”
Section: Discussionsupporting
confidence: 46%
“…Currently, it is not clear how precisely androgen induces AR nuclear translocation. Once the AR is in the nucleus, it will assemble a mega-protein transcription complex, which is a dynamic process including transient recruitment and then dissociation of co-factors, chromatin remodeling molecules, proteasome subunits and general transcription machinery (reviewed in Heinlein and Chang, 2004). We recently showed that PI3K inhibitors could not block AR nuclear translocation but suppressed AR-mediated gene expression (Liao et al, 2004), indicating that a PI3K-dependent mechanism is involved in AR-DNA binding, or the assembly of AR-mediated transcription complex.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of expression of VEGF has been proposed to lead to decreased vasculature, resulting in apoptosis of the luminal cells. 13 Although the initial response to androgen ablation is encouraging, resulting in apoptotic cell death and PCA regression, it is followed by development of aggressive HR disease. This process may vary in the length of time, ranging from a few months to 2 or 3 years.…”
Section: Androgens Maintain and Stimulate The Prostate Glandmentioning
confidence: 99%